PENGARUH MEDIA EXPOSURE, FOREIGN OWNERSHIP, UKURAN DEWAN KOMISARIS, DAN TIPE INDUSTRI TERHADAP CORPO-RATE SOCIAL RESPONSIBILITY DISCLOSURE - Ni Luh Made Nabila Prajna Paramitha (2022)
Corporate Social Responsibility is the contribution of the company or the business world to sustainable economic development, with an emphasis on economic, social and environmental aspects. This study is a quantitative study which aims to examine the effect of Media Exposure, Foreign Ownership, Size of the Board of Commissioners, and Industry Type on Corporate Social Responsibility Disclosure. This study uses secondary data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020. The sampling criteria were taken using the pur-posive sampling method, which was obtained with a total of 140 samples. The sample data was obtained from the Indonesia Stock Exchange (IDX). Hypothesis testing in this study uses multiple linear regression models. The model was processed and tested using Microsoft Excel and STATA software. The results of this study are Media Exposure and Industry Type have no effect on Corporate Social Responsibility Disclosure, while Foreign Ownership and Board of Commissioners Size have a positive and significant effect on Corporate Social Responsibility Disclosure.